The Effect Of Providing Incentives On Employee Performance In The Public Works And Spatial Planning Office Asahan Regency - Ilham Bahruddin; Muhammad Isa Indrawan (Yayasan Multidimensi Kreatif, 2024)
This study was a quantitative associative causal research aimed at analyzing the relationship between variables and determining the effect of two independent (exogenous) variables on the dependent variable. The research was conducted at the Public Works and Spatial Planning Office of Asahan Regency, with a population of 68 employees. The sampling technique used was saturated sampling, where all members of the population were selected as the sample. The data used were obtained through questionnaires distributed to respondents consisting of employees from various divisions. The results of the study showed that the provision of incentives had a positive and significant effect on employee performance. This was evidenced by the t-count value of 10.368, which was greater than the t-table value of 1.99656, with a significance value of 0.000, which was less than 0.05. The regression coefficient of 0.901 indicated that each 1-point increase in the provision of incentives would lead to a 0.901-point increase in employee performance, assuming other variables remained constant. Additionally, the results of the coefficient of determination test showed an Adjusted R Square value of 0.862 or 86.20%, indicating that the provision of incentives had a very high effect on employee performance, with the remaining 13.80% influenced by other factors not examined in this study. Overall, the findings of this study identified that increasing the provision of incentives could contribute to improving employee performance at the Public Works and Spatial Planning Office of Asahan Regency.